A Prospective Study on Association of Prostatic Calcifications with Sexual Dysfunction in Men with Chronic Prostatitis/Chronic Pelvic Pain Syndrome (CP/CPPS). (16th April 2014) - Zhao, Zhigang; Xuan, Xujun; Zhang, Jingwei; He, Jun; Zeng, Guohua
Abstract Introduction Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common debilitating condition of unclear etiology. Sexual dysfunction is an important component of the clinical phenotype of CP/CPPS. Patients often have prostatic calcifications, but a link to sexual dysfunction is unknown. Aim The aim of this study was to evaluate the association of prostatic calcifications with sexual dysfunction in this condition. Methods A total of 358 males with CP/CPPS were consecutively enrolled, and a prospectively maintained database of these patients was analyzed. Calcifications were diagnosed using ultrasound imaging of the prostate. Symptom severity was measured using the National Institutes of Health Chronic Prostatitis Symptom Index (CPSI). Sexual dysfunction was evaluated using the validated 15‐item International Index of Erectile Function (IIEF‐15) questionnaire and 5‐item Premature Ejaculation Diagnostic Tool scales. The variables were compared between patients with prostatic calcifications and those without using the Student's t‐test, Wilcoxon unpaired test, or chi‐square test. Main Outcome Measure Logistic regression models were developed to explore a possible association between prostatic calcifications and sexual dysfunction. Results Measurable calcifications in the prostate were found in 175 (48.9%) of the 358 patients. Patients with calcifications were more likely to have higher white blood cell counts or positive bacteria cultures in their prostatic fluid, longer symptoms duration, and lower scores for the total IIEF‐15, IIEF‐erectile function, and IIEF‐intercourse satisfaction domains (P < 0.001 for each). However, the scores for CPSI, premature ejaculation, and IIEF‐orgasmic function, IIEF‐sexual desire, and IIEF‐overall satisfaction domains were identical between men with and without calcifications (P > 0.05 for each). Furthermore, logistic regression analyses revealed that intraprostatic calcification is significantly associated with self‐assessed erectile dysfunction (ED) (odds ratio:3.632, 95% confidence interval: 2.405–5.822, P < 0.001). Conclusion Our results showed that prostatic calcifications are significantly associated with the presence of ED in CP/CPPS males. Zhao Z, Xuan X, Zhang J, He J, and Zeng G. A prospective study on association of prostatic calcifications with sexual dysfunction in men with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). J Sex Med 2014;11:2528–2536.